Emergency repair of upper extremity large soft tissue and vascular injuries with flow-through anterolateral thigh free flaps. (December 2017) - Zhan, Yi; Fu, Guo; Zhou, Xiang; He, Bo; Yan, Li-Wei; Zhu, Qing-Tang; Gu, Li-Qiang; Liu, Xiao-Lin; Qi, Jian
Abstract: Background/Objectives: Complex extremity trauma commonly involves both soft tissue and vascular injuries. Traditional two-stage surgical repair may delay rehabilitation and functional recovery, as well as increase the risk of infections. We report a single-stage reconstructive surgical method that repairs soft tissue defects and vascular injuries with flow-through free flaps to improve functional outcomes. Methods: Between March 2010 and December 2016 in our hospital, 5 patients with severe upper extremity trauma received single-stage reconstructive surgery, in which a flow-through anterolateral thigh free flap was applied to repair soft tissue defects and vascular injuries simultaneously. Cases of injured artery were reconstructed with the distal trunk of the descending branch of the lateral circumflex femoral artery. A segment of adjacent vein was used if there was a second artery injury. Patients were followed to evaluate their functional recoveries, and received computed tomography angiography examinations to assess peripheral circulation. Results: Two patients had post-operative thumb necrosis; one required amputation, and the other was healed after debridement and abdominal pedicle flap repair. The other 3 patients had no major complications (infection, necrosis) to the recipient or donor sites after surgery. All the patients had achieved satisfactory functional recovery by the end of the follow-up period. Computed tomography angiography showed adequate circulation in the peripheral vessels. Conclusions: The success of these cases shows that one-step reconstructive surgery with flow-through anterolateral thigh free flaps can be a safe and effective treatment option for patients with complex upper extremity trauma with soft tissue defects and vascular injuries. Highlights: ALT flap is one of the best choice for reconstruction of large soft tissue defects. Flow-through flap can repair vascular defects without disrupting donor sites. Emergency repair is feasible in the selection of appropriate cases.